Facies interpretation from well logs: Applied to SMEKS field, offshore western Niger Delta (2012)
This paper presents the interpretation of data from well-logs and core samples obtained from SMEKS Field, offshore western Niger Delta. The study aims at using well log approach in establishing the sedimentary facies, their successions and environments of deposition in this field. In addition, a well to well correlation and reservoir quality assessment were undertaken. The palaeodepositional environments in the field were deduced by combining gamma ray log trends with core data. Lithofacies interpretation was carried out with Schlumberger’s Petrel 2010 software package using the gamma ray, effective porosity and resistivity logs obtained from four wells. Correlation technique was used to delineate the subsurface trends of these facies. Lithofacies calculation shows that the entire well interval consists of sand, silt and shale. Four log facies were recognized in the study area: irregular log trends representing deep marine clay; a funnel-shaped facies representing a crevasse splay; a cylindrical-shaped facies representing slope channel-fills and turbidite fans, and a bell-shaped facies representing transgressive marine shelf. Four reservoir bodies were discovered in the field. Sand bodies are 50 m thick or less and are characteristically poorly sorted to well sorted, fine clayey sands-with some conglomerate and shale pebbles. A qualitative reservoir evaluation shows that porosity values range from 20 to 37% while the permeability range from 524 to 9600 md. The porosity and permeability are better developed in areas of sand bodies deposited in the slope channel environment. There is a good hydrocarbon bearing potential of the deep sea channel sands coupled with the complex fault system of which the distal Niger Delta province is associated.